Bringing Virtual Communities into a Marketing Strategy to Create Purchase Intentions in the Social Media Era - Risca Fitri Ayuni (Journal of Indonesian Economy and Business (JIEB), 2020)
Introduction/main objectives: A virtual community is a new form of social interaction that provides an alternative way for connectivity and creativity. As the most favorite platform, social networking site is one of marketing objectives and strategies for global brands. The purpose of this study is to examine the antecedents (social eWOM, image, and trust) and consequences (purchase intention) of eWOM’s adoption. Background problem: Today, taking part in virtual communities is a must. People with the same interests share their experiences and become trustworthy referees for others. Understanding the effect virtual communities can have will help companies to expand their markets. Novelty: Social eWOM has a great impact, but no prior studies have examined the effect of social eWOM or a virtual community on image, trust, eWOM‘s adoption and purchase intentions, this study would be the first study that provides a comprehensive model using recent issues. Research methods: Purposive sampling was used to recruit 240 active participants in virtual communities in Indonesia. To collect the data, spreading questionnaire was conducted. SPSS and PLS 3 were used to analyze the data. Findings: The findings proved the relationship among social eWOM, image and trust. It also revealed that eWOM’s adoption affected purchase intentions. Surprisingly, image has no statistically significant effect on eWOM’s adoption. Conclusion: Well-managed social eWOM creates a better image, and increases trust, and eWOM’s adoption leads to an increase in the purchase intention. This study offers managerial insights to manage social eWOM from any virtual communities, to improve their image and trust. Finally, managers should maintain positive reviews, as this will also create an intention to purchase.